1987
DOI: 10.1103/physrevlett.59.1776
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an even-denominator quantum number in the fractional quantum Hall effect

Abstract: An even-denominator rational quantum number has been observed in the Hall resistance of a twodimensional electron system. At partial filling of the second Landau level v=2+ y = y and at temperatures below 100 mK, a fractional Hall plateau develops at p xy =(h/e 2 )/y defined to better than 0.5%. Equivalent even-denominator quantization is absent in the lowest Landau level under comparable conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
958
4
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,074 publications
(994 citation statements)
references
References 15 publications
23
958
4
9
Order By: Relevance
“…3(b), and extract a quasigap from the temperature dependence of S, as shown in Fig. 3 (c [24,26,27]. The evolution of R xx with temperature at ν = 6/5 clearly shows such behavior.…”
Section: Fig 1 (A)mentioning
confidence: 89%
“…3(b), and extract a quasigap from the temperature dependence of S, as shown in Fig. 3 (c [24,26,27]. The evolution of R xx with temperature at ν = 6/5 clearly shows such behavior.…”
Section: Fig 1 (A)mentioning
confidence: 89%
“…A vast array of states has now been observed where, in general, ν takes an odd denominator as a result of the Pauli exclusion principle. The most remarkable exception to this has been the FQHE at ν = 5/2 in GaAs heterostructures 137 . Its most widely accepted explanation is that an attractive interaction occurs between composite fermions within the second Landau level, owing to the nodal nature of the electronic wavefunction.…”
Section: Quantum Computingmentioning
confidence: 99%
“…When the direction of the magnetic field B is tilted, the orbital LL splitting is given by the field component B ⊥ normal to the two-dimensional electron system (2DES) while the total field strength B determines the Zeeman splitting E Z . Early experiments on GaAs revealed that the ν = 4/3, 5/3, and 8/5 states behaved differently upon tilting the sample [4,5]: While the ν = 4/3 and 8/5 states were undergoing a transition from a spinunpolarized state to a polarized one, the ν = 5/3 state was always fully spin polarized.Although the FQHE has been reported in quite a number of different materials [6][7][8][9][10][11][12], the FQHE has never been observed in a diluted magnetic semiconductor in which atoms with magnetic moment (e.g., Mn 2+ ) are placed in a 2DES. Then, the localized spins in the magnetic impurities' d orbitals interact with the correlated electron system via the quantum mechanical s-d exchange interaction, causing giant Zeeman splitting [13] which is tunable in magnitude, sign, and field dependence [14].…”
mentioning
confidence: 99%